Comorbidities in Chronic Kidney Disease (CKD) - Jankowski, Joachim; Noels, Heidi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
With a mean worldwide prevalence of 13%, chronic kidney disease imposes a massive health burden on our society. In addition to reduced kidney function, patients with chronic kidney disease increasingly suffer from cardiovascular diseases affecting the heart and vasculature. Cardiovascular diseases account for around half of the deaths of patients with advanced chronic kidney disease. However, therapeutic options are highly insufficient. The pathological mechanisms that underlie increased cardiovascular risk in patients with chronic kidney disease remain largely unknown. This Special Issue provides insights into comorbidities in CKD patients, mainly focused on increased cardiovascular risk, and summarizes current knowledge of underlying pathophysiological mechanisms.